Seduced by Mrs. Robinson how The Graduate became the touchstone of a generation - Gray, Beverly (Algonquin Books of Chapel Hill, 2017)
"An exploration of The Graduate's influence on filmmaking and how the movie both reflected and changed a generation's views of sex, work, and marriage"--
Keywords: The graduate; Graduate (Motion picture) / Influence; Graduate (Motion picture) / History and criticism; Graduate (Motion picture); Motion pictures / Influence; Identity (Psychology) in motion pictures; ART / Film & Video; PERFORMING ARTS / Film / History & Criticism; SOCIAL SCIENCE / Popular Culture; Influence (Literary, artistic, etc.); Criticism, interpretation, etc